'It's not just about the dinner; it's about everything else that we do': A qualitative study exploring how Meals on Wheels meet the needs of self‐isolating adults during COVID‐19. (12th November 2021) - Papadaki, Angeliki; Ali, Becky; Cameron, Ailsa; Armstrong, Miranda E. G.; Isaacs, Paul; Thomas, Kali S.; Gadbois, Emily A.; Willis, Paul
Abstract: Meals on Wheels (MoWs), a service offered by local authorities in England, deliver meals to older, housebound and/or vulnerable adults, who might otherwise not be able to acquire and prepare their own meals. Research suggests that MoWs provide benefits beyond nutrition. Little is known about the actual interactions between service providers and clients, particularly during the COVID‐19 pandemic. The aim of this small‐scale, formative study was to explore MoWs service providers' experiences and their perceptions around the benefits and challenges faced by the service, and understand how these experiences changed during the first UK national lockdown. Semi‐structured interviews were conducted in September 2020 with 18 service providers of MoWs (drivers who deliver the meals, service coordinators and managers) in two local authorities in England, and analysed thematically. Participants indicated that benefits of the service encompassed those to clients (e.g. welfare checks, encouraging independence and identifying and addressing isolation and loneliness), employees (e.g. sense of pride, rewarding relationships with clients) and the wider community (e.g. reducing pressures on families), and described MoWs as the 'fourth emergency service' (e.g. being the first responders to emergency situations). Participants identified several challenges faced by the MoWs service, including organisational challenges (e.g. funding cuts and closures, lack of appropriate publicity to raise awareness of the service) and restrictions on time spent with clients. The pandemic and lockdown resulted in increased demand on resources, concerns about client and staff wellbeing and uncertainty about how the service will cope if lockdowns continue. These findings provide important insights regarding the wide benefits of MoWs and the challenges the service faces, which can be used as the formative research base to guide future interventions and policies to protect vulnerable adults, not only during the COVID‐19 pandemic, but beyond.